PENGARUH BRAND AWARNESS DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI BRAND SKINTIFIC PADA MAHASISWI PASCASARJANA UNIVERSITAS SANGGA BUANA YPKP BANDUNG ANGKATAN 2024/2025 - Rachmat, Andri Kusmayadi; Amanda, Dea; Astuti, Melani Tri; Ramadhan, Mochamad Zibran Haykal; Shabrina, Nadia Sarah; Yanti, Neneng Trisna; Hasibuan, Puji Lestari; Sikki, Nurhaeni (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This research aims to analyze the influence of brand awareness and online customer reviews on the purchase interest in Skintific beauty products among postgraduate students of Universitas Sangga Buana YPKP Bandung, class of 2024/2025. The research method used is quantitative with a survey approach, involving a sample of 98 respondents selected purposively. Data were collected through an online questionnaire consisting of measurement scales for brand awareness, online customer reviews, and purchase intention. The research results show that brand awareness has a positive and significant impact on purchase interest, where the higher the consumer awareness of the Skintific brand, the greater their interest in buying the product. In addition, online customer reviews were also found to have a positive and significant impact on purchase intention, where online customer reviews play an important role in shaping trust and purchase decisions. Regression analysis shows that both variables, brand awareness and online customer review, simultaneously have a significant impact on consumer purchase intention. This research underscores the importance of marketing strategies that prioritize increasing brand awareness and managing online reviews to drive purchase interest among young consumers, particularly among postgraduate female students. These findings have implications for Skintific's management in designing more effective marketing campaigns in the digital era.